Psychological Distress and Perceived Life Changes Among College Students During the COVID-19 Pandemic: The Moderating Roles of Family Support and Gender - Jennifer Parker; Julia Rothenberg; Larry Musolino; Nicole Ryerson; Michelle Kaschak; Teresa Kistler (COVID)
Objective: To examine associations among psychological distress, perceptions of life changes, and perceptions of family support among college students during the quarantine period of the pandemic. Background: A supportive family can buffer psychological distress during crises. During the early months of the COVID-19 pandemic, many college students abruptly returned to their family home, disrupting a developmental stage typically oriented toward independence and peer connection. While previous research has highlighted the stressors of this period, less is known about the role of perceived family support in shaping students’ mental health outcomes. Method: Data from a cross-sectional sample of 339 college students were collected. Statistical analysis included a hierarchical multiple regression and moderated moderation to investigate the relationship between the life changes college students experienced due to COVID-19 and distress and how family support moderated this relationship while treating gender as a secondary moderator. Results: Perceptions of worsening life conditions due to COVID-19 were associated with higher levels of distress and vice versa. Perceptions of emotional forms of family support moderated this relationship, but only among male participants. Conclusions: This study contributes to our understanding of the mental health implications of the pandemic on college students by identifying emotional family support as a gender-specific protective factor. Implications: Insights from this study may inform mental health interventions that consider family dynamics and gender-specific coping during large-scale crises. These findings may also guide strategies for supporting students facing the long-term psychological impacts of the COVID-19 pandemic.